PENGEMBANGAN CONTEXTUAL E-FLIP BOOK BERBAHASA ARAB UNTUK MENINGKATKAN KEMAMPUAN BAHASA ARAB SISWA MADRASAH IBTIDAIYAH (MI) - Iman Matin; Nur Luthfi Rizqa Herianingtyas; Izzah Muyassaroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Arabic language learning at MI is not yet optimal, namely the availability of supporting media and open materials is still limited. The use of contextual as an open material in Arabic language learning has great potential to increase the effectiveness of the learning process. E-Flip Book is a digital technology innovation that makes conventional books more dynamic with an attractive and interactive format, equipped with animation, sound and other multimedia features. This research aims to develop a contextually based Arabic E-flip Book to improve MI students' Arabic language skills. This research is a Research and Development (R&D) model of Borg & Gall (2003). This research was carried out by implementing seven of the ten stages of the Borg & Gall model. Data collection techniques used in this research include observation and interviews as an analysis of e-flipbook development needs and questionnaire techniques for product validation by media experts, language experts and content experts. The results of the assessment from material experts on the Arabic E-Flipbook for Class I Students at MI obtained a percentage result of 80% and was included in the "Decent" category. The media validation results were 82% and included in the "Very Eligible" category. The results of language expert acquisition were 72% and were included in the "Decent" category.